Shrimp Parvovirus Circular DNA Fragments Arise From Both Endogenous Viral Elements and the Infecting Virus - Taengchaiyaphum, Suparat; Buathongkam, Phasini; Sukthaworn, Suchitraporn; Wongkhaluang, Prapatsorn; Sritunyalucksana, Kallaya; Flegel, Timothy William (Frontiers in Immunology, 2021)
Some insects use endogenous reverse transcriptase (RT) to make variable viral copy DNA (vcDNA) fragments from viral RNA in linear (lvcDNA) and circular (cvcDNA) forms. The latter form is easy to extract selectively. The vcDNA produces small interfering RNA (siRNA) variants that inhibit viral replication via the RNA interference (RNAi) pathway. The vcDNA is also autonomously inserted into the host genome as endogenous viral elements (EVE) that can also result in RNAi. We hypothesized that similar mechanisms occurred in shrimp. We used the insect methods to extract circular viral copy DNA (cvcDNA) from the giant tiger shrimp (Penaeus monodon) infected with a virus originally named infectious hypodermal and hematopoietic necrosis virus (IHHNV). Simultaneous injection of the extracted cvcDNA plus IHHNV into whiteleg shrimp (Penaeus vannamei) resulted in a significant reduction in IHHNV replication when compared to shrimp injected with IHHNV only. Next generation sequencing (NGS) revealed that the extract contained a mixture of two general IHHNV-cvcDNA types. One showed 98 to 99% sequence identity to GenBank record AF218266 from an extant type of infectious IHHNV. The other type showed 98% sequence identity to GenBank record DQ228358, an EVE formerly called non-infectious IHHNV. The startling discovery that EVE could also give rise to cvcDNA revealed that cvcDNA provided an easy means to identify and characterize EVE in shrimp and perhaps other organisms. These studies open the way for identification, characterization and use of protective cvcDNA as a potential shrimp vaccine and as a tool to identify, characterize and select naturally protective EVE to improve shrimp tolerance to homologous viruses in breeding programs.